Effects of acupuncture therapy in diabetic neuropathic pain: A systematic review and meta-analysis - Xintong Li; Yang Liu; Zheng Jing; Baozhu Fan; Weimin Pan; Shigang Mao; Yabing Han (Elsevier, 2023)
Objective: To evaluate the effectiveness of acupuncture in relieving diabetic neuropathic pain and to establish a more reliable and efficient foundation for acupuncture practice in diabetes care. Methods: The Chinese National Knowledge Infrastructure, Wanfang database, Chongqing Weipu, Chinese Biomedical Literature Database, PubMed, Embase, and Cochrane Library were all searched for a randomized controlled trial research of acupuncture for DNP. Two researchers independently performed literature screening, quality evaluation, and data extraction. After selecting studies and extracting data, we conducted the data analysis using RevMan 5.4 and Stata 14.0. The quality was assessed using the Cochrane Risk of Bias Assessment Tool. Results: An extensive review of 19 studies involving 1276 patients up to April 29, 2023, found that acupuncture was successful in improving pain intensity [MD= −1.09; 95% CI (−1.28, −0.89), P < 0.00001], clinical efficacy indicating pain changes [RR= 1.22; 95% CI (1.15, 1.29), P < 0.00001], and clinical neuropathy [MD= −1.55; 95% CI ( −3.00, −0.09), P = 0.04] in DNP patients. Quality of life was also improved, with few side effects reported. Conclusion: According to this meta-analysis, acupuncture therapy significantly improved the clinical efficacy of pain intensity, pain changes, and clinical neuropathy in patients with DNP, improved the quality of life of patients to a certain extent, and had lower side effects. This discovery provides evidence-based and practical recommendations for the treatment of DNP patients.